Preparation method and application of fluorosilane modified silicon dioxide aerogel

By adding fluorosilane to the silica aerogel for one-step modification, the problems of insufficient strength and toughness and surface hydrophilicity were solved, and the hydrophobicity and mechanical properties were improved, and excellent isolation was maintained. Thermal ability.

CN119461388APending Publication Date: 2025-02-18TIANJIN UNIV

Patent Information

Application Number
CN202411532665.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In actual applications, silica aerogels have problems such as insufficient strength and toughness, and surface hydrophilicity leads to water absorption and icing, which limits their thermal insulation performance.

Method used

One-step modification is achieved by adding fluorosilane during co-hydrolysis and aging, fluorine elements are used to enhance the hydrophobicity of the aerogel, and the bonding strength between the silica particles is enhanced by the introduction of flexible chains.

Benefits of technology

The hydrophobicity and mechanical properties of silica aerogel are improved, the compressive strength and toughness are enhanced, and the excellent thermal insulation ability is maintained, while simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461388A_ABST
    Figure CN119461388A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a preparation method and application of fluorosilane modified silicon dioxide aerogel. Fluorosilane is used for modifying silicon dioxide aerogel through a one-step method, and fluorosilane is used as a co-precursor and an aging modifier to be added in the preparation process, so that the hydrophobicity is improved, and meanwhile, the mechanical property is enhanced. The hydrophobic property of a solid is controlled by surface chemistry and morphology, fluorosilane is introduced into the silicon dioxide aerogel, and due to introduction of fluorine, the hydrophobic property of the silicon dioxide aerogel is changed into super-hydrophobic property from general hydrophobic property, and the contact angle reaches 152 degrees; the bonding strength of silicon dioxide particles is enhanced by introducing a micromolecular alkyl chain, so that the strength and toughness of the aerogel are improved, the breaking strength is increased to 1.2 MPa, and the breaking deformation is increased to 22%; in addition, the heat conductivity coefficient of the modified aerogel is less than 30.0 mW / (m.K). Huge potential exists in the aspects of heat insulation, heat preservation and self-cleaning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of fluorosilane-modified silica aerogel and its related characterization in thermal insulation applications. In particular, it relates to a preparation method and application of fluorosilane-modified silica aerogel. More specifically, it relates to a preparation method of fluorosilane-modified silica aerogel by a one-step method and its practical application in thermal insulation and super-hydrophobicity. Background Art

[0002] Most of the commonly used thermal insulation materials have a loose and porous structure, which can effectively hinder the convection heat conduction between gases. Silica aerogel is a relatively common thermal insulation material. The so-called aerogel refers to a special material in which the liquid in the wet gel is replaced by air and its original pore structure is maintained. The silica aerogel skeleton is composed of SiO 2 Nanoparticles agglomerate to form a continuous irregular three-dimensional porous network, in which the particles are connected by Si-O-Si bonds, and the pores inside the network are filled with air. The air molecules are located in the nanopores. The smaller the pore size, the worse the air fluidity. When the air does not flow, the gas molecules are adsorbed on the surface of the pore wall, and a vacuum state is formed inside the pores, thereby reducing the thermal convection phenomenon. Because of the special structure of aerogel, it can effectively reduce heat transfer and thermal convection, thereby reducing thermal conductivity. At present, silica aerogel is often used in the form of aerogel felt, aerogel sheet and aerogel coating. It is widely used in military, aerospace, petrochemical and other fields. It can not only be used for pipeline protection at ultra-low temperatures to reduce energy loss, but also for safety protection at ultra-high temperatures.

[0003] SiO 2 Aerogel was first prepared in 1931 by Kistler of Stanford University in the United States using the sol-gel method and supercritical drying technology. In 1985, Tewari et al. used TEOS, which is much less toxic than TMOS, as a precursor and used CO 2 Supercritical drying was used to produce silica aerogels of equivalent quality. This improvement not only reduced the toxicity of the silicon source, but also greatly reduced the risks of supercritical drying.

[0004] As research deepens, the demand for silica aerogel modification continues to grow, and it becomes more and more urgent to improve the possibility of aerogel implementation in practical applications. However, the shortcomings of silica aerogel itself limit its application. First of all, since silica aerogel is mostly composed of air, the skeleton is composed of randomly connected silica nanoparticles, which leads to greater brittleness and poor strength and toughness. In addition, the surface of pure silica aerogel is relatively hydrophilic, and it is easy to absorb water and freeze during low-temperature applications, thereby reducing the thermal insulation performance. Therefore, the purpose of application is currently mainly achieved by improving the strength and hydrophobicity of aerogel. The mechanical properties of silica aerogels can be improved by the following methods: (i) using organosiloxanes such as methyltrimethoxysilane as precursors to prepare polyorganosilicone silsesquioxane aerogels; (ii) cross-linking the silica skeleton with polymers such as epoxides, polyimides and isocyanates to attach the polymers to the surface of the silica skeleton and increase the contact area between nanoparticles; (iii) adding a three-dimensional fiber network to the silica aerogel; (iiii) incorporating inorganic substances is also a feasible method to enhance the mechanical properties of silica aerogels. There are two main methods to improve hydrophobicity. One is to increase hydrophobicity by adding silanizing agents (such as hexamethyldisiloxane, methyltrimethoxysilane, phenyltrimethoxysilane, etc.) during the sol-gel process; the second method is to change the surface of the dried aerogel by reacting with ethanol in the gas phase to form ethoxy groups. In order to improve the mechanical properties and hydrophilicity of silica aerogel, in this patent, we add organic macromolecular fluorosilane during the co-hydrolysis and aging process. Due to the introduction of fluorine, the hydrophobicity of the aerogel surface is enhanced; at the same time, the introduced flexible chain will attach to the silica skeleton, enhance the bonding strength between particles, and improve the strength and toughness of the aerogel. Only one-step modification is required to obtain silica aerogel with improved mechanical properties and hydrophobicity. The doped monomers can be directly co-hydrolyzed and co-condensed without separate pre-polymerization operations, which is easy to operate. Summary of the invention

[0005] In the present invention, fluorosilane is used to modify silica aerogel in a one-step process. Fluorosilane is added to the preparation process as a co-precursor and an aging modifier, respectively, to improve the hydrophobicity and enhance the mechanical properties. The hydrophobicity of solids is controlled by surface chemistry and morphology, which can be quantified using a water contact angle, which depends on the size of the intermolecular interaction between the surface and the contacting liquid. Solid surfaces that exhibit a water contact angle of more than 150° are considered to be superhydrophobic. The hydrolysis antennae of the aerogel surface in this patent can reach 152°, which meets the superhydrophobic characteristics, thereby satisfying the function of fluorosilane-modified aerogels for daily antifouling. In addition, the thermal conductivity of pure silica aerogel is 18.5mW / (m·K), and after adding fluorosilane, the thermal conductivity is about 23mW / (m·K), while the thermal conductivity modified by organic polymer is about 40mW / (m·K). Compared with other methods, the thermal conductivity increment of fluorosilane-modified aerogel is smaller, but it still has excellent thermal insulation ability. Moreover, this method is simple and convenient, easy to operate, low-cost, and easy to compound with fiber felt, etc. It only needs to be vacuum impregnated for a period of time during the sol process, and it is expected to be mass-produced to a certain extent.

[0006] The purpose of the present invention is to provide a method for preparing fluorosilane-modified silica aerogel, so as to improve the mechanical properties and hydrophobicity of silica-based aerogel and increase the feasibility in practical applications.

[0007] The technical solution of the present invention is as follows:

[0008] The preparation method of fluorosilane-modified silica aerogel comprises the following steps:

[0009] 1) Fluorosilane as a co-precursor: Tetraethyl silicate (TEOS), water and ethanol are mixed and stirred evenly, and then an acidic catalyst is added to adjust the pH of the system to about 2-3, and then the fluorosilane is added to the silica sol for co-hydrolysis, and the hydrolysis is stirred at room temperature for 5-10 hours under sealed conditions; after the hydrolysis is completed, an alkaline catalyst is added to adjust the pH to 6-8, and the solution is allowed to stand at room temperature to wait for gelation; after gelation, the wet gel is immersed in an aging solution mixed with tetraethyl silicate and ethanol, and then aged in an oven for 24-48 hours to promote further reinforcement of the silica skeleton;

[0010] or:

[0011] Fluorosilane as an aging modifier: Tetraethyl silicate (TEOS), water and ethanol are mixed and stirred evenly, then an acidic catalyst is added to adjust the pH of the system to about 2-3, and the mixture is stirred and hydrolyzed at room temperature for 5-8 hours under sealed conditions; after the hydrolysis is completed, an alkaline catalyst is added to adjust the pH to 6-8, and the mixture is allowed to stand at room temperature to wait for gelation; after gelation, the wet gel is immersed in an aging solution mixed with fluorosilane and ethanol, and then aged in an oven for 24-48 hours to promote further reinforcement of the silica skeleton;

[0012] 2) Solvent replacement: The gel was taken out of the oven, cooled naturally to room temperature, and then ethanol was added to perform solvent replacement to remove unreacted tetraethyl silicate, fluorosilane and excess water;

[0013] 3) Supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 240-245°C, it is kept at this temperature for 1-2 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0014] Preferably, in step 1, the molar ratio of the fluorosilane in the common precursor method to the silicon dioxide in the system is 1% to 30%;

[0015] Preferably, the fluorosilane in step 1 includes trifluoropropyltrimethoxysilane, triethoxy[4-(trifluoromethyl)phenyl]silane, tridecafluorooctyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, perfluorooctyltrichlorosilane, nonafluorohexyltrimethoxysilane, triethoxy[5,5,6,6,7,7,7-heptafluoro-4,4-bis(trifluoromethyl)heptyl]silane;

[0016] Preferably, the acid catalyst in step 1 can be hydrochloric acid, nitric acid, acetic acid, or oxalic acid, and the base catalyst can be ammonia water, propylene oxide, tetramethylammonium hydroxide, or 3-aminopropyltriethoxysilane;

[0017] Preferably, the aging solution in the co-precursor method of step 1 is a mixed solution of tetraethyl silicate and ethanol in a volume ratio of 1:5 to 1:10, and the aging time is 12 to 48 hours.

[0018] Preferably, the aging solution in the aging modification method of step 1 is a mixed solution of fluorosilane and ethanol in a volume ratio of 1:5 to 1:10, and the aging time is 12 to 48 hours.

[0019] Preferably, the solvent replacement in step 2 is performed every 5 to 8 hours, for a total of 3 to 6 times.

[0020] In the method of the present invention, fluorosilane is introduced into the silica aerogel. Due to the introduction of fluorine element, the hydrophobicity of the silica aerogel is changed from general hydrophobicity to super hydrophobicity, and the contact angle reaches 152°; the introduced small molecule alkyl chain enhances the bonding strength of the silica particles, thereby improving the strength and toughness of the aerogel, the fracture strength is increased to 1.2MPa, and the fracture deformation is increased to 22%; in addition, the thermal conductivity of the modified aerogel is less than 30.0mW / (m·K).

[0021] The fluorosilane-modified silica aerogel of the present invention is used in thermal insulation.

[0022] Application of the fluorosilane-modified silica aerogel of the present invention in self-cleaning.

[0023] When fluorosilane-modified silica aerogel is applied to -100°C and 200°C environments, the surface temperature of the aerogel in contact with the air environment is approximately 15°C and 65°C, which has good thermal insulation capabilities.

[0024] The present invention and its application in thermal insulation and self-cleaning. Through a one-step modification method, fluorosilane and silicon source are used as co-precursors. When the gel is formed, the fluorine on the alkyl chain is exposed outside the pores, thereby improving the hydrophobicity; at the same time, since the alkyl chain is attached to the surface of the gel, it plays a buffering role when subjected to external force, thereby improving its compressive strength and toughness. The aerogel prepared by the technical solution proposed by the present invention has the characteristics of simple operation, mild reaction conditions, easy availability of raw materials and low thermal conductivity, and has great potential in future thermal insulation.

[0025] Compared with the existing pure silica aerogel, the technical solution of the present invention successfully prepared silica aerogel with improved mechanical properties and hydrophobicity. Since the hydrophobicity of the aerogel has changed from general hydrophobicity to super hydrophobicity, it can be used in anti-fouling, anti-corrosion and anti-icing in daily life. In addition, for pure silica aerogel, since it is only randomly connected by nanoparticles, the skeleton is relatively fragile. The small molecule fluorosilane introduced in this solution can be attached to the surface of the silica nanoparticle skeleton, which will play a buffering role when subjected to external force, so that the compressive strength of the aerogel increases from 0.4MPa to 1.2MPa, and the fracture deformation increases from 10% to 22%, effectively enhancing the toughness and strength of the aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope photo of the silica aerogel prepared in Example 1

[0027] Figure 2 This is the EDS image of the silica aerogel prepared in Example 2

[0028] Figure 3 The thermal conductivity of the aerogels prepared in Examples 3-5 and Comparative Example is

[0029] Figure 4 The mechanical properties test diagram of the aerogels prepared in Examples 6-8 and Comparative Examples

[0030] Figure 5 This is a photo of the contact angle of silicon dioxide prepared in Example 9.

[0031] Figure 6 This is the infrared thermal imaging image of the silica aerogel prepared in Implementation 10

[0032] Figure 7 This is a self-cleaning test diagram of the silica aerogel prepared in Example 11 DETAILED DESCRIPTION

[0033] Example 1

[0034] Step 1, weigh 10.2g tetraethyl silicate (TEOS), 22.3g ethanol and 3.5g water respectively, wherein the molar amount of silica in the system is 9.0%, mix the three evenly and stir for 10min, add acetic acid dropwise to adjust the pH of the system to about 2-3, then add 0.11g trifluoropropyltrimethoxysilane to the silica sol for co-hydrolysis, the content is 1% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 6h. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-7, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of tetraethyl silicate and ethanol of 1:5 and age it in a 50°C oven for 24h to promote further reinforcement of the silica skeleton.

[0035] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 8 hours for a total of 3 times.

[0036] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 240°C, it is kept at this temperature for 1 hour, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0037] Test Example 1

[0038] In this test example, the microscopic morphology of the thermal insulation material prepared in Example 1 was observed, and the microscopic morphology of the porous thermal insulation material prepared in Example 1 was tested using an S-4800 cold field emission scanning electron microscope. Figure 1The SEM photograph of the aerogel prepared in Example 1 shows that it is in the shape of a pearl chain, the overall pore distribution is relatively uniform, and there is no obvious phase separation, which proves that the fluorosilane and the original silicon source are well combined.

[0039] Example 2

[0040] Step 1, weigh 25.3g tetraethyl silicate (TEOS), 48.1g ethanol and 8.5g water respectively, wherein the molar amount of silica in the system is 8.8%, mix the three evenly and stir for 10min, add oxalic acid dropwise to adjust the pH of the system to about 2-3, then add 1.85g triethoxy [4- (trifluoromethyl) phenyl] silane to the silica sol for co-hydrolysis, the content is 5% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 6h. After the hydrolysis is completed, add propylene oxide dropwise to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:6 and age it in a 60°C oven for 24h to promote further reinforcement of the silica skeleton.

[0041] Step 2, solvent replacement: take out the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Change the solvent every 6 hours for a total of 4 times.

[0042] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 243°C, it is kept at this temperature for 1.5 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0043] Test Example 2

[0044] In this test example, the aerogel prepared in Example 2 was subjected to microscopic morphology testing using an S-4800 cold field emission scanning electron microscope to test the porous thermal insulation material prepared in Example 1. Figure 2 This is an elemental analysis EDS image of the thermal insulation material prepared in Example 2 of the present invention, in which the fluorine element is evenly distributed, which advantageously proves that fluorine is incorporated into the silica aerogel.

[0045] Example 3

[0046] Step 1, weigh 30.0g tetraethyl silicate (TEOS), 66.1g ethanol and 10.2g water respectively, wherein the molar amount of silica in the system is 8.1%, mix the three evenly and stir vigorously for 10min, add hydrochloric acid dropwise to adjust the pH of the system to about 2-3, then add 8.63g tridecafluorooctyl trimethoxysilane to the silica sol for co-hydrolysis, the content is 13% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 8h. After the hydrolysis is completed, tetramethylammonium hydroxide is added dropwise to adjust the pH to 6-8, and the gel is allowed to stand at room temperature. After gelation, the wet gel is immersed in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:8 and aged in an oven at 70°C for 24h to promote further reinforcement of the silica skeleton.

[0047] Step 2, solvent replacement: take out the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Change the solvent every 7 hours for a total of 4 times.

[0048] Step 3 Supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 245°C, it is kept at this temperature for 1.4 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature inside the reactor drops to room temperature, the prepared aerogel can be taken out.

[0049] Test Example 3

[0050] In this test example, the thermal conductivity of the aerogels prepared in Examples 3-5 and the unmodified silica aerogels was measured. Specifically, the thermal conductivity of the thermal insulation materials prepared in the examples and the comparative examples was measured using a TC2120 thermal conductivity tester. Figure 3 The thermal conductivity results of the aerogels of the comparative example and Examples 3-5 are shown in FIG. The thermal conductivity of the prepared aerogels is low and has good thermal insulation performance. The thermal conductivity of the aerogels prepared in the comparative example and Examples 3, 4, and 5 are 18.5 mW / (m·K), 20.5 mW / (m·K), 24.7 mW / (m·K), and 26.2 mW / (m·K), respectively.

[0051] Example 4

[0052] Step 1, weigh 20.5g tetraethyl silicate (TEOS), 52.2g ethanol and 6.9g water respectively, wherein the molar amount of silica in the system is 7.4%, wherein the molar amount of silica in the system is 7.4%, mix the three evenly and stir vigorously for 10min, add nitric acid dropwise to adjust the pH of the system to about 2-3, then add 6.51g nonafluorohexyltrimethoxysilane to the silica sol for co-hydrolysis, the content is 18% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 12h. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-7, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:10 and age it in an oven at 55°C for 24h to promote further reinforcement of the silica skeleton.

[0053] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 5 hours for a total of 6 times.

[0054] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 242°C, it is kept at this temperature for 1.8 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0055] Example 5

[0056] Step 1, weigh 15.2g tetraethyl silicate (TEOS), 48.3g ethanol and 6.5g water respectively, wherein the molar amount of silica in the system is 6.2%, mix the three evenly and stir vigorously for 20min, add nitric acid dropwise to adjust the pH of the system to about 2-3, then add 7.66g perfluorooctyltrichlorosilane to the silica sol for co-hydrolysis, the content is 22% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 5h. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:9 and age it in a 70°C oven for 24h to promote further reinforcement of the silica skeleton.

[0057] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 8 hours for a total of 3 times.

[0058] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 244°C, it is kept at this temperature for 1.6 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0059] Example 6

[0060] Step 1, weigh 42.3g tetraethyl silicate (TEOS), 93.4g ethanol and 21.9g water respectively, wherein the molar amount of silica in the system is 7.7%, mix the three evenly and stir vigorously for 15min, add oxalic acid dropwise to adjust the pH of the system to about 2-3, then add 12.35g heptafluorodecyl triethoxysilane to the silica sol for co-hydrolysis, the content is 10% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 12h. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-7, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:10 and age it in an oven at 60°C for 24h to promote further reinforcement of the silica skeleton.

[0061] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 5 hours for a total of 6 times.

[0062] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 241°C, it is kept at this temperature for 1.2 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out. After the solvent replacement is completed, supercritical drying is performed to obtain the prepared aerogel.

[0063] Test Example 4

[0064] In this test example, the mechanical properties of the aerogels prepared in Examples 6-8 and the comparative example (unmodified silica aerogel) were tested. Specifically, a CMT4203 microcomputer-controlled electronic universal testing machine was used to perform compression tests on the aerogel materials prepared in the examples and comparative examples. Before the test, the sample surface was polished flat with 1000-mesh sandpaper. The fracture strengths of the aerogels prepared in the comparative example and Examples 6, 7, and 8 were 0.4 MPa, 0.75 MPa, 1.2 MPa, and 0.78 MPa, respectively.

[0065] Example 7

[0066] Step 1, weigh 10.2g tetraethyl silicate (TEOS), 22.5g ethanol and 3.7g water respectively, wherein the molar amount of silica in the system is 7.6%, mix the three evenly and stir vigorously for 10min, add hydrochloric acid dropwise to adjust the pH of the system to about 2-3, then add 7.635g triethoxy [5,5,6,6,7,7,7-heptafluoro-4,4-bis (trifluoromethyl) heptyl] silane to the silica sol for co-hydrolysis, the content is 30% of the molar amount of silica in the system, and finally stir and hydrolyze at room temperature under sealed conditions for 12h. After the hydrolysis is completed, 3-aminopropyl triethoxysilane is added dropwise to adjust the pH to 6-7, and the solution is left to stand at room temperature to wait for gelation. After gelation, the wet gel is immersed in an aging solution with a volume ratio of tetraethyl silicate to ethanol of 1:8 and aged in an oven at 75°C for 24h to promote further reinforcement of the silica skeleton.

[0067] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 8 hours for a total of 3 times.

[0068] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 240°C, it is kept at this temperature for 1.6 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0069] Example 8

[0070] Step 1, weigh 30.5g of tetraethyl silicate, 68.5g and 12.6g of water respectively, wherein the molar amount of silicon dioxide in the system is 8.1%, mix the three evenly and stir for 10 minutes, add hydrochloric acid dropwise to adjust the pH of the system to about 2-3, and stir and hydrolyze at room temperature for 6 hours under sealed conditions. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of ethoxy [4- (trifluoromethyl) phenyl] silane and ethanol of 1:6 and age it in a 60°C oven for 48 hours to promote further reinforcement of the silica skeleton.

[0071] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 8 hours for a total of 3 times.

[0072] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 243°C, it is kept at this temperature for 1.7 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0073] Example 9

[0074] Step 1, weigh 50.2g of tetraethyl silicate, 127.5g and 17.9g of water respectively, of which the molar amount of silicon dioxide in the system is 7.4%, mix the three evenly and stir for 10 minutes, add nitric acid dropwise to adjust the pH of the system to about 2-3, and stir and hydrolyze at room temperature for 6 hours under sealed conditions. After the hydrolysis is completed, add ammonia water to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of nonafluorohexyltrimethoxysilane and ethanol of 1:7 and age it in a 75°C oven for 36 hours to promote further reinforcement of the silica skeleton.

[0075] Step 2, solvent replacement: take out the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Change the solvent every 7 hours for a total of 4 times.

[0076] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 244°C, it is kept at this temperature for 1.9 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature inside the reactor drops to room temperature, the prepared aerogel can be taken out.

[0077] Test Example 5

[0078] This test example is to test the hydrophobicity of the aerogel prepared in Example 9, and specifically adopts a JC200D optical contact angle tester to measure the angle. Figure 5 This is a photo of the contact angle of the aerogel prepared in Example 9, with an angle of 152°.

[0079] Example 10

[0080] Step 1, weigh 29.2g of tetraethyl silicate, 80.2g and 15.8g of water respectively, of which the molar amount of silicon dioxide in the system is 6.7%, mix the three evenly and stir for 10 minutes, add acetic acid dropwise to adjust the pH of the system to about 2-3, and stir and hydrolyze at room temperature for 6 hours under sealed conditions. After the hydrolysis is completed, add tetramethylammonium hydroxide dropwise to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of trifluoropropyltrimethoxysilane and ethanol of 1:9 and age it in a 70°C oven for 30 hours to promote further reinforcement of the silica skeleton.

[0081] Step 2, solvent replacement: remove the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Replace the solvent every 8 hours for a total of 3 times.

[0082] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 240°C, it is kept at this temperature for 2.0 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0083] Test Example 6

[0084] This test example is to test the thermal insulation performance of the aerogel prepared in Example 10 and the comparative example (unmodified silica aerogel). The specific operation is to take an aerogel with a height of about 10 mm, place it on a hot table at 200°C and a cold table at -120°C, respectively, and then use an infrared thermal imager to record the temperature change on the upper surface of the aerogel.

[0085] Figure 6 These are infrared thermal imaging photographs of the aerogels prepared in Example 10 and the comparative example after being stabilized on a hot stage at 200°C and a cold stage at -120°C for 10 minutes (the left is the comparative example, and the right is Example 10). The thermal insulation properties of the unmodified silica aerogel and the modified aerogel are not much different, proving that although the mechanical properties are increased after modification, the thermal insulation properties of the aerogel are not affected, and the aerogel still has excellent thermal insulation capabilities.

[0086] Embodiment 11

[0087] Step 1, weigh 25.3g of tetraethyl silicate, 68.5g and 8.6g of water respectively, of which the molar amount of silicon dioxide in the system is 7.1%, mix the three evenly and stir for 10 minutes, add oxalic acid dropwise to adjust the pH of the system to about 2-3, and stir and hydrolyze at room temperature for 6 hours under sealed conditions. After the hydrolysis is completed, add 3-aminopropyltriethoxysilane to adjust the pH to 6-8, and stand at room temperature to wait for gelation. After gelation, soak the wet gel in an aging solution with a volume ratio of trifluoropropyltrimethoxysilane and ethanol of 1:9 and age it in a 70°C oven for 30 hours to promote further reinforcement of the silica skeleton.

[0088] Step 2, solvent replacement: take out the gel from the oven, wait for it to cool naturally to room temperature, add fresh and clean ethanol, and perform solvent replacement to remove unreacted TEOS and excess water. Change the solvent every 7 hours for a total of 5 times.

[0089] Step 3, supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 245°C, it is kept at this temperature for 1.0h, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

[0090] Test Example 7

[0091] This test example is to prove that the improved hydrophobic properties of the modified aerogel give it a certain self-cleaning ability. Specifically, the aerogels prepared in Example 11 and the comparative example were immersed in a methylene blue solution for 1 minute, and then taken out to observe the surface changes of the two. Figure 7 The self-cleaning performance test of the aerogels prepared in Example 11 and the comparative example (unmodified silica aerogel) (top: comparative example; bottom: Example 11) was performed by Figure 7 It can be seen that the aerogel of the comparative example has blue residual liquid after immersion, while the aerogel of Example 11 is still clean and stain-free, proving that the hydrophobicity of the silica aerogel is improved after modification.

[0092] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A method for preparing fluorosilane-modified silica aerogel, characterized in that: The steps include: 1) Fluorosilane as a co-precursor: tetraethyl silicate, water and ethanol are mixed and stirred evenly, and then an acidic catalyst is added to adjust the system pH to about 2-3, and then the fluorosilane is added to the silica sol for co-hydrolysis, and the hydrolysis is stirred at room temperature for 5-10 hours under sealed conditions; after the hydrolysis is completed, an alkaline catalyst is added to adjust the pH to 6-8, and the solution is allowed to stand at room temperature to wait for gelation; after gelation, the wet gel is immersed in an aging solution mixed with tetraethyl silicate and ethanol, and then aged in an oven for 24-48 hours to promote further reinforcement of the silica skeleton; or: Fluorosilane as an aging modifier: Tetraethyl silicate, water and ethanol are mixed and stirred evenly, then an acidic catalyst is added to adjust the pH of the system to about 2-3, and the mixture is stirred and hydrolyzed at room temperature for 5-8 hours under sealed conditions; after the hydrolysis is completed, an alkaline catalyst is added to adjust the pH to 6-8, and the mixture is allowed to stand at room temperature to wait for gelation; after gelation, the wet gel is immersed in an aging solution mixed with fluorosilane and ethanol, and then aged in an oven for 24-48 hours to promote further reinforcement of the silica skeleton; 2) Solvent replacement: The gel was taken out of the oven, cooled naturally to room temperature, and then ethanol was added to perform solvent replacement to remove unreacted tetraethyl silicate, fluorosilane and excess water; 3) Supercritical drying: After the solvent replacement is completed, the container in which the sample is completely immersed in ethanol is placed in an ethanol supercritical drying reactor for supercritical drying. After the critical temperature of ethanol reaches 240-245°C, it is kept at this temperature for 1-2 hours, and then the ethanol vapor inside the reactor is released until the internal and external pressures are balanced; finally, when the temperature in the reactor drops to room temperature, the prepared aerogel can be taken out.

2. The method according to claim 1, characterized in that: In step 1, the molar ratio of the fluorosilane in the common precursor method to the silicon dioxide in the system is 1% to 30%.

3. The method according to claim 1, characterized in that: The fluorosilane in step 1 includes trifluoropropyltrimethoxysilane, triethoxy[4-(trifluoromethyl)phenyl]silane, tridecafluorooctyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, perfluorooctyltrichlorosilane, nonafluorohexyltrimethoxysilane or triethoxy[5,5,6,6,7,7,7-heptafluoro-4,4-bis(trifluoromethyl)heptyl]silane.

4. The method according to claim 1, characterized in that: The acid catalyst in step 1 uses hydrochloric acid, nitric acid, acetic acid, or oxalic acid; the base catalyst uses ammonia water, propylene oxide, tetramethylammonium hydroxide, or 3-aminopropyltriethoxysilane.

5. The method according to claim 1, characterized in that: The aging solution in the co-precursor method of step 1 is a mixed solution of tetraethyl silicate and ethanol in a volume ratio of 1:5 to 1:10, and the aging time is 12 to 48 hours.

6. The method according to claim 1, characterized in that: The aging solution in the aging modification method of step 1 is a mixed solution of fluorosilane and ethanol in a volume ratio of 1:5 to 1:10, and the aging time is 12 to 48 hours.

7. The method according to claim 1, characterized in that: The solvent replacement in step 2 is performed every 5 to 8 hours, for a total of 3 to 6 times.

8. Application of the fluorosilane-modified silica aerogel prepared by the method of claim 1 in thermal insulation.

9. Application of the fluorosilane-modified silica aerogel prepared by the method of claim 1 in self-cleaning.

Citation Information

Patent Citations

  • Preparation method of organic silicon aerogel with super-amphiphobic performance

    CN112646229A

  • Preparation method of gradient-density hydrophobic silica aerogel

    CN112875711A

  • Preparation method of in-situ fluorination modified super-amphiphobic flexible SiO2 aerogel

    CN113830772A

  • Method for preparing silicon dioxide aerogel based on low-concentration modifier

    CN117658154A

  • Silica aerogel and its production

    JP2001072408A

Cited By

  • Heat insulation window film and preparation method thereof

    CN120191102A